2011
DOI: 10.1039/c0ja00215a
|View full text |Cite
|
Sign up to set email alerts
|

A study on gold and copper provenance for Romanian prehistoric objects using micro-SR XRF

Abstract: This study intends to clarify the metal provenance of gold archaeological items using the variation of the Au-Ag ratio and the presence of trace elements as Sn, Sb, Te, and Pb, concentrating on gold Dacian Koson coins, recovered recently. It also extends the area of our investigations to the copper provenance of Bronze Age artifacts-axes, sickles, and celts-found on Romanian territory. The experiments were performed by micro-SR XRF at BESSY Berlin, at the BAM-line facility. Two types of coins (Koson, with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…A number of the more interesting articles are noted below. Constantinescu et al 38 employed m-SR XRF spectrometry to measure the trace elements in gold and copper Romanian archaeological items to clarify their provenance. The elemental evidence from the gold coins (Pb, Sb, Sn and Te) indicated that the gold coins with a monogram were made from refined gold and the ones without a monogram were made from native (alluvial) Transylvanian gold.…”
Section: Non-ferrous Metals and Alloysmentioning
confidence: 99%
“…A number of the more interesting articles are noted below. Constantinescu et al 38 employed m-SR XRF spectrometry to measure the trace elements in gold and copper Romanian archaeological items to clarify their provenance. The elemental evidence from the gold coins (Pb, Sb, Sn and Te) indicated that the gold coins with a monogram were made from refined gold and the ones without a monogram were made from native (alluvial) Transylvanian gold.…”
Section: Non-ferrous Metals and Alloysmentioning
confidence: 99%
“…X-ray fluorescence microscopy ( µ -XRF) is an ideally suited technique for high-resolution imaging of metal based pigments. Its outstanding capabilities in terms of spatial resolution and elemental sensitivity have been demonstrated for the analysis of pigments in cultural heritage samples, such as masterpiece paintings 6 8 , handwritings 9 , 10 , metal artefacts 11 , 12 and other solid objects 13 . Here, we present the first study employing high-resolution µ -XRF for the in-situ analysis of pigments within a textile sample with high historical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…A suitable method for quantitative element-specific analyses with high spatial resolution is X-ray fluorescence microscopy ( μ -XRF) [ 16 18 ]. The method has proven its value for elemental mapping in cultural heritage studies, regarding, for example, paintings [ 19 22 ], inks [ 23 , 24 ], and solid objects [ 25 , 26 ], and also enables a detailed investigation of oxidation states by performing X-ray absorption near edge spectroscopy (XANES) [ 27 31 ]. Although many biological tissues are prone to decomposition upon X-ray radiation [ 32 34 ], sheep wool and other keratin based biofibres are relatively stable to significant X-ray doses and are not expected to be structurally destroyed during standard μ -XRF mapping [ 35 ].…”
Section: Introductionmentioning
confidence: 99%